GLOBALISASI KONTEMPORER DAN FEMINISME TRANSNASIONAL DIGITAL: ANALISIS JARINGAN TEKSTUAL @jakartafeminist - Rifka Annisa Hermanto (Fakultas Seni Rupa dan Desain ITB, 2022)
The internet and social media have influenced how feminist activists work today. In Indonesia, digital feminist activism was found to have been initiated by young women to deconstruct the general view related to women's empowerment, gender equality, networking, and mobilizing the protest constituents to the street. The opening of networks between countries by the internet has the potential to be the